Development and validation of questionnaires for eating‐related distress among advanced cancer patients and families. Issue 1 (20th November 2022) - Amano, Koji; Morita, Tatsuya; Miura, Tomofumi; Mori, Naoharu; Tatara, Ryohei; Kessoku, Takaomi; Matsuda, Yoshinobu; Tagami, Keita; Otani, Hiroyuki; Mori, Masanori; Taniyama, Tomohiko; Nakajima, Nobuhisa; et al.
Abstract: Background: Eating‐related distress (ERD) is one type of psychosocial distress among advanced cancer patients and family caregivers. Its alleviation is a key issue in palliative care; however, there is no validated tool for measuring ERD. Methods: The purpose of this study was to validate tools for evaluating ERD among patients and family caregivers. The study consisted of a development and validation/retest phase. In the development phase, we made preliminary questionnaires for patients and family caregivers. After face validity and content validity, we performed an exploratory factor analysis and discussed the final adoption of items. In the validation/retest phase, we examined factor validity with an exploratory factor analysis. We calculated Pearson's correlation coefficients between the questionnaire for patients, the Functional Assessment of Anorexia/Cachexia Therapy Anorexia Cachexia Subscale (FAACT ACS) and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Cachexia 24 (EORTC QLQ‐CAX24) and Pearson's correlation coefficients between the questionnaire for family caregivers and the Caregiver Quality of Life Index‐Cancer (CQOLC) for concurrent validity. We calculated Cronbach's alpha coefficients (Cronbach's alpha) and intraclass correlation coefficients (ICCs) for internal consistency and test–retest reliability. We performed the Mann–Whitney U test between the questionnaires and cancer cachexia based on criteria from the international consensus for known‐group validity. Results: In the development phase, 162 pairs of patients and family caregivers were asked to participate, and 144 patients and 106 family caregivers responded. In the validation/retest phase, 333 pairs of patients and family caregivers were asked to participate, and 234 patients and 152 family caregivers responded. Overall, 183 patients and 112 family caregivers did the retest. Seven conceptual groups were extracted for the ERD among patients and family caregivers, respectively. Patient factors 1–7 correlated with FAACT ACS ( r = −0.63, −0.43, −0.55, −0.40, −0.38, −0.54, −0.38, respectively) and EORTC QLQ‐CAX24 ( r = 0.58, 0.40, 0.60, 0.49, 0.38, 0.59, 0.42, respectively). Family factors 1–7 correlated with CQOLC ( r = −0.34, −0.30, −0.37, −0.37, −0.46, −0.42, −0.40, respectively). The values of Cronbach's alpha and ICC of each factor and all factors of patients ranged from 0.84 to 0.96 and 0.67 to 0.83, respectively. Those of each factor and all factors of family caregivers ranged from 0.84 to 0.96 and 0.63 to 0.84, respectively. The cachexia group of patients had significantly higher scores than the non‐cachexia group for each factor and all factors. Conclusions: Newly developed tools for measuring ERD experienced by advanced cancer patients and family caregivers have been validated.